Disruption of the ammonium transporter AMT1.1 alters basal defenses generating resistance against Pseudomonas syringae and Plectosphaerella cucumerina - Pastor, Victoria; Gamir, Jordi; Camañes, Gemma; Cerezo, Miguel; Sánchez-Bel, Paloma; Flors, Victor (Frontiers in Plant Science, 2014)
Disruption of the high-affinity nitrate transporter NRT2.1 activates the priming defense against Pseudomonas syringae, resulting in enhanced resistance. In this study, it is demonstrated that the high-affinity ammonium transporter AMT1.1 is a negative regulator of Arabidopsis defense responses. The T-DNA knockout mutant amt1.1 displays enhanced resistance against Plectosphaerella cucumerina and reduced susceptibility to P. syringae. The impairment of AMT1.1 induces significant metabolic changes in the absence of challenge, suggesting that amt1.1 retains constitutive defense responses. Interestingly, amt1.1 combats pathogens differently depending on the lifestyle of the pathogen. In addition, N starvation enhances the susceptibility of wild type plants and the mutant amt1.1 to P. syringae whereas it has no effect on P. cucumerina resistance. The metabolic changes of amt1.1 against P. syringae are subtler and are restricted to the phenylpropanoid pathway, which correlates with its reduced susceptibility. By contrast, the amt1.1 mutant responds by activating higher levels of camalexin and callose against P. cucumerina. In addition, amt1.1 shows altered levels of aliphatic and indolic glucosinolates and other Trp-related compounds following infection by the necrotroph. These observations indicate that AMT1.1 may play additional roles that affect N uptake and plant immune responses.